Invasão e estabelecimento de Digitonthophagus gazella (Fabricius) (Coleoptera: scarabaeidae) em fragmento de transição cerrado-mata atlântica - Angotti, Marina Acero (2014)
Digitonthophagus gazella is known worldwide because it has been introduced in tropical and subtropical regions of several countries. The aim of this introduction was to assist in the removal of dung pats in pasture areas and to aid in the biological control of flies of veterinary importance. Thus, although D. gazella has a preference for open and sunny habitats and herbaceous vegetation, there is evidence that it apparently has been adapting to closed-canopy areas. Therefore, this study aimed at evaluating the ability of D. gazella to develop in a forest environment. The study was conducted in 2012 and 2013 in the Farm of UNESP - Ilha Solteira in Mato Grosso do Sul, Brazil. To evaluate the presence of D. gazella in the forest were used pitfall traps and to verify its capability of develop in this habitat couples of this species were kept in pasture and forest fragment in the absence and presence of competitors. The results indicate that D. gazella is able to enter the forest fragment, but at short distances from the edge. Additionally, D. gazella was not able to develop and establishment in the forest fragment.